Dead soldier covered in snow laying in the snow - De Santis, Giuseppe, 1917-1997 (Z. Smith Reynolds Library, Wake Forest University, 1965)
This film depicts the unfortunate aggression of Mussolini into the Soviet Union during World War II. Between 1941-1943, against the advice of his generals and his ally, Adolf Hitler, Mussolini ordered 250,000 Italian troops into the Soviet Union.
Keywords: Kennedy, Arthur, 1914-1990; Motion picture actors and actresses -- Italy; Motion picture producers and directors -- Italy; Motion pictures -- Italy -- History -- Sources; Pisu, Raffaele; Prokhorenko, Zhanna, 1940-; Samoilova, Tatiana, 1934-; Soldiers -- Italy -- Drama; Stills (motion pictures); World War, 1939-1945 -- Campaigns -- Soviet Union -- Drama; World War, 1939-1945 -- Italy -- Drama.